PENGARUH HARGA, PROMOSI DAN CABANG/PERWAKILAN TERHADAP PENINGKATAN PENJUALAN MOBIL TOYOTA AVANZA PADA PT. HADJI KALLA CABANG ALAUDDIN MAKASSAR - Muh. Indra Fauzi Ilyas (AkMen JURNAL ILMIAH, 2016)
This study aimed to analyze the influence of price policy, promotions and branches / representative to the increased sales of Toyota Avanza At PT. Hadji Kalla Alauddin Makassar Branch and to determine the most dominant factor affecting the increase in car sales Toyota Avanza in PT. Hadji Kalla Makassar. The analytical method used in this research is descriptive analysis and multiple linear regression analysis. The results showed that the results of calculations with multiple linear regression analysis with SPSS obtained F count equal to 12 295 with a probability level of 0.000 (significant) and also the probability of much less than 0.05, meaning that the factor price policies, promotions and branches / representative affect the Toyota Avanza car sales at PT. Hadji Kalla Branch Alauddin Makassar. With the prominence of these three variables explained that before making a purchasing decision of Toyota Avanza, consumers consider strategies based on the turnover of products offered price policy, promotions, branch / representative.